The Role of Emerging Technologies in Enhancing Inclusive and Equitable Education - Anwar Mehdi; Karim Yassine Darwish (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Emerging technologies play a crucial role in transforming education by fostering inclusivity and equity. This study explores how artificial intelligence, virtual reality, and adaptive learning platforms contribute to overcoming traditional barriers to education. The research adopts a qualitative approach, analyzing case studies and recent advancements in educational technology. Findings reveal that these technologies enhance accessibility for students with disabilities, provide personalized learning experiences, and bridge educational gaps in underprivileged regions. The study highlights the importance of policy support and infrastructure development to maximize the benefits of technological integration in education. The implications suggest that adopting emerging technologies can create a more inclusive and equitable learning environment, ensuring education for all.